2005
DOI: 10.1203/01.pdr.0000155944.48195.97
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Antenatal Inflammation and Antenatal Infection Identified by Detection of Microbial Genes by Polymerase Chain Reaction

Abstract: Although antenatal infection is thought to play an important role in the pathogenesis of preterm labor and neonatal diseases, the exact mechanisms are largely unknown. We sought to clarify the relationship between antenatal infection and intrauterine and neonatal inflammation. Samples were obtained from 41 preterm infants of Ͻ33 wk gestation delivered to 36 mothers and analyzed for the presence of 16s ribosomal RNA (16s rRNA) genes using PCR and for the proinflammatory cytokines IL-6 and IL-8. In 16 (44%) moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 58 publications
(42 reference statements)
4
81
0
Order By: Relevance
“…Because their study design allowed them to enroll more infants with a low risk for BPD, it is likely that it underestimated the impact of Ureaplasma species in increasing the risk of developing BPD. Miralles et al reported in their preliminary study that there was no association between the presence of microbes in neonatal and/or placental specimens and the development of BPD (15). This study has some similarities with ours, but differed in that it was designed to investigate the significance of microbes and not Ureaplasma species.…”
Section: Articlesmentioning
confidence: 52%
See 2 more Smart Citations
“…Because their study design allowed them to enroll more infants with a low risk for BPD, it is likely that it underestimated the impact of Ureaplasma species in increasing the risk of developing BPD. Miralles et al reported in their preliminary study that there was no association between the presence of microbes in neonatal and/or placental specimens and the development of BPD (15). This study has some similarities with ours, but differed in that it was designed to investigate the significance of microbes and not Ureaplasma species.…”
Section: Articlesmentioning
confidence: 52%
“…The bacterial 16S rRNA gene was detected using the methods described previously (15,16). Briefly, the extracted DNA was amplified by PCR using the FD1 (AGA GTT TGA TCC TGG CTC AG) and rP1 (ACG G(T/A/C)T ACC TTG TTA CGA CTT) primers.…”
Section: Detection Of Ureaplasma Species and Other Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed mechanisms for infectious causes of recurrent abortion include: direct infection of the uterus, fetus, or placenta; placental insufficiency; chronic endometritis or endocervicitis; amnionitis; infected intrauterine device [18,19]. Ureaplasma can be detected in the cervix or vagina of 40-80% of sexually mature asymptomatic women [20]. U. parvum may play important role in pregnancy and eliciting conditions associated with prematurity [21].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of bacterial presence, the aspirates were shown to contain swallowed amniotic fluid, and thus have been proposed as an alternative to investigate fetal infections associated with adverse pregnancy outcomes (Miralles et al, 2005;GonzalesMarin et al, 2012). In our previous studies, F. nucleatum was observed at high levels in the neonatal samples (up to 2.32610 3 cells ml…”
Section: Introductionmentioning
confidence: 99%